Communicating with the dead: lipids, lipid mediators and extracellular vesicles. (19th June 2018) - Devitt, Andrew; Griffiths, Helen R.; Milic, Ivana
Abstract : Apoptosis is a key event in the control of inflammation. However, for this to be successful, dying cells must efficiently and effectively communicate their presence to phagocytes to ensure timely removal of dying cells. Here, we consider apoptotic cell-derived extracellular vesicles and the role of contained lipids and lipid mediators in ensuring effective control of inflammation. We discuss key outstanding issues in the study of cell death and cell communication, and introduce the concept of the ' active extracellular vesicle ' as a metabolically active and potentially changing intercellular communicator.